The influence of firearms trafficking on gunshot injuries in a co-offending network. (August 2020) - Ciomek, Alexandra M.; Braga, Anthony A.; Papachristos, Andrew V.
Abstract: Individuals at the greatest risk of gunshot victimization are often prohibited from legally acquiring guns in the U.S. due to prior felony convictions or other disqualifications. Prohibited persons often rely on others – such as friends, family members, fellow gang members, and gun brokers – to acquire firearms. This study examines whether the sources of guns recovered from high-risk individuals differ relative to the sources of guns recovered more generally in a major U.S. city, and whether illegally-diverted guns are associated with increased gunshot victimization risk. Using official data, we recreate the co-offending network of individuals in Boston who were arrested or contacted by the police with at least one other person between 2007 and 2014. Firearms trace data are then used to develop measures of the shortest distance between individuals and firearms in their immediate network. Results suggest guns with markers of illegal diversion are more likely to be recovered in the highest risk sector of the network and that the probability of gunshot victimization increases with decreased distance to an individual linked to firearms with markers of illegal trafficking. Highlights: Network analysis enhances understanding of the concentration of victimization risk. Network proximity to guns increases individual risk of gunshot victimization. The guns of high risk individuals are substantially different from other guns. Guns of high risk individuals include more characteristics of illegal trafficking. Network access to guns with markers of illegal trafficking is especially dangerous.